2019
DOI: 10.5194/os-15-1225-2019
|View full text |Cite
|
Sign up to set email alerts
|

<i>p</i>CO<sub>2</sub> variability in the surface waters of the eastern Gulf of Cádiz (SW Iberian Peninsula)

Abstract: Abstract. Spatio-temporal variations in the partial pressure of CO2 (pCO2) were studied during eight oceanographic cruises conducted between March 2014 and February 2016 in surface waters of the eastern shelf of the Gulf of Cádiz (SW Iberian Peninsula) between the Guadalquivir river and Cape Trafalgar. pCO2 presents a range of variation between 320.6 and 513.6 µatm with highest values during summer and autumn and lowest during spring and winter. For the whole study, pCO2 shows a linear dependence with temperat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 128 publications
0
3
0
1
Order By: Relevance
“…This decomposition is well known and extensively used at regional and global scale (e.g. Landschützer et al, 2018;Jiménez-López et al, 2019;Ko et al, 2021).…”
Section: Thermal and Non-thermal Contributions To Surface Pcomentioning
confidence: 99%
“…This decomposition is well known and extensively used at regional and global scale (e.g. Landschützer et al, 2018;Jiménez-López et al, 2019;Ko et al, 2021).…”
Section: Thermal and Non-thermal Contributions To Surface Pcomentioning
confidence: 99%
“…Recent studies have focused on the role coastal zones play in the CO 2 flux ocean-atmosphere (fCO 2 ), given how scarce information is for these zones (Laruelle et al 2014, Jiménez-López et al 2019. Coastal zones play a considerable role in the global carbon cycle due to high primary production and coastal processes such as upwelling (Gattuso et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Estudios recientes se han centrado en el papel que juegan las zonas costeras en el flujo de CO 2 océano-atmósfera (fCO 2 ), puesto que la información para estas zonas es escasa (Laruelle et al 2014, Jiménez-López et al 2019. Las zonas costeras juegan un rol considerable en el ciclo de carbono global debido a la producción primaria alta y los procesos costeros como las surgencias (Gattuso et al 1998).…”
Section: Introductionunclassified
“…The strong physical-biogeochemical interactions result in large spatial and temporal variations of sea surface pCO 2 in coastal oceans, making it challenging to quantify carbon fluxes in coastal environments. Estimates based on available data showed that the coastal ocean could either act as a sink (DeGrandpre et al, 2002;Hales et al, 2005;Borges et al, 2006;Chen and Borges, 2009;Hales et al, 2012;Jiang et al, 2013;Turi et al, 2014;Evans et al, 2019;Jiménez-López et al, 2019) or source (Friederich et al, 2002;Borges et al, 2005;Wang et al, 2005;Xue et al, 2012;Robbins et al, 2018;Li et al, 2020) for atmospheric CO 2 depending on the dominant controlling mechanism of sea surface pCO 2 in a specific system.…”
Section: Introductionmentioning
confidence: 99%